Non-invasive diagnosis and biomarkers in alcohol-related liver disease - Moreno, Christophe; Mueller, Sebastian; Szabo, Gyongyi (Journal of hepatology, 2019)
Even though alcohol-related liver disease (ALD) is a major cause of severe liver disease worldwide, most patients with ALD are diagnosed at the decompensation stage. Liver biopsy is still considered the gold standard for establishing a definite diagnosis and assessing the fibrosis stage of ALD, but it is an invasive procedure, associated with significant morbidity. During the last decade, non-invasive tests have been developed to estimate the severity of liver fibrosis and steatosis. Measurement of liver stiffness by transient elastography has become the most commonly used non-invasive parameter to evaluate fibrosis. In ALD, transient elastography has been demonstrated to have an excellent performance to detect advanced fibrosis and cirrhosis. However, aspartate aminotransferase levels must be considered when interpreting liver stiffness cut-offs. Non-invasive biological tests have also been evaluated to assess liver fibrosis in ALD. The commercially available Enhanced Liver Fibrosis test and FibroTest have comparable performance for the diagnosis of advanced fibrosis in ALD, with studies suggesting that they are better than other biological tests (i.e. FIB-4 and APRI). Although ultrasound is still accepted as an initial screen for fatty liver diagnosis, new methods have recently been developed to detect steatosis. Magnetic resonance spectroscopy and magnetic resonance imaging techniques are highly accurate and reproducible, with superior sensitivities and specificities for detecting histological steatosis than ultrasound. However, low availability and high cost limit the use of magnetic resonance techniques in routine clinical practice. More recently, controlled attenuation parameter was developed as a novel tool to non-invasively assess liver steatosis; performed in combination with transient elastography, it was suggested to be superior to regular ultrasound for detecting steatosis and was shown to have acceptable diagnostic accuracy. New serum biomarkers are under investigation to non-invasively diagnose more severe forms of ALD and to predict prognosis of patients.